2013
DOI: 10.1128/jcm.02366-12
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing of Candida tropicalis Shows the Presence of Different Clonal Clusters and Fluconazole Susceptibility Profiles in Sequential Isolates from Candidemia Patients in São Paulo, Brazil

Abstract: fThe profiles of 61 Candida tropicalis isolates from 43 patients (28 adults and 15 children) diagnosed with candidemia at two teaching hospitals in São Paulo, Brazil, were characterized by multilocus sequence typing (MLST). For the 14 patients who had bloodstream infections, 32 isolates were serially collected from their blood and/or catheters. Thirty-nine diploid sequence types (DSTs) were differentiated. According to the C. tropicalis MLST database (http://pubmlst.org/ctropicalis/), 36 DSTs and 23 genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 46 publications
1
22
0
1
Order By: Relevance
“…Although DST168, previously reported only from Taiwan, was found in Kuwait, DST164 which was also detected in Taiwan and was previously shown to be associated with 5-flucytosine resistance [ 43 ] was not detected in our study and the single 5-flucytosine-resistant isolate (Kw45-15) from Kuwait belonged to a new DST (DST719). Furthermore, DST238, which was shared between two isolates originating from vaginal and percutaneous endoscopic gastrostomy specimens in Kuwait, has previously been described for two bloodstream isolates from Brazil [ 46 ]. Our data reinforce previous observations suggesting lack of association between different DSTs with antifungal resistance, specimen type or geographical location and support both shared and unique features among geographic populations of C .…”
Section: Discussionmentioning
confidence: 99%
“…Although DST168, previously reported only from Taiwan, was found in Kuwait, DST164 which was also detected in Taiwan and was previously shown to be associated with 5-flucytosine resistance [ 43 ] was not detected in our study and the single 5-flucytosine-resistant isolate (Kw45-15) from Kuwait belonged to a new DST (DST719). Furthermore, DST238, which was shared between two isolates originating from vaginal and percutaneous endoscopic gastrostomy specimens in Kuwait, has previously been described for two bloodstream isolates from Brazil [ 46 ]. Our data reinforce previous observations suggesting lack of association between different DSTs with antifungal resistance, specimen type or geographical location and support both shared and unique features among geographic populations of C .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent epidemiologic study conducted by Maganti and colleagues [ 25 ], nosocomial clusters have been shown to represent 33% of total isolates causing candidemia in Canadian hospitals. Using MLST analysis, the genetic relatedness of Candida isolates has been assessed in two Brazilian studies of candidemia, in which different clusters have been found among isolates of C. albicans [ 24 ] and C. tropicalis [ 65 ]. Our present study reinforces the utility of sequence polymorphism analysis for evaluating the relationships among Candida species and its application for examining the molecular epidemiology of fungal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 14 patients with multiple isolates, seven had microvariation in a single gene from sequential isolates and three had microvariation in six gene fragments. Finally, they identified three isolates resistant to fluconazole but did not find any correlation between this resistance and the isolate clustering (195).…”
Section: Candida Tropicalismentioning
confidence: 94%
“…Jacobsen et al also found that multiple isolates from a given patient shared the same MLST profile or showed evidence of microevolution, such as loss of heterozygosity (194). Magri et al studied the genetic diversity of 61 isolates from 43 patients hospitalized in Brazil (195), reporting 39 DSTs. Among the 14 patients with multiple isolates, seven had microvariation in a single gene from sequential isolates and three had microvariation in six gene fragments.…”
Section: Candida Tropicalismentioning
confidence: 99%